MENTORING PRACTICES IN ENGLISH LANGUAGE: A SUPPORTIVE ENVIRONMENT FOR STUDENTS OF EFL - dos Santos, Antonio Genário Pinheiro; Santos, Giovana Silva; Silva, Leandro de Souza (Revista Docência e Cibercultura, 2022)
This paper aims to discuss the development of the teaching project Mentoring Practices in English Language: a supportive environment for students of EFL, under the effects and circumstances of the remote teaching context. Focused on the systematic monitorship of contents and related knowledge, this project seeks to offer, in the Portuguese-English language program at Felcs/UFRN, pedagogical support for students in their freshman and sophomore years who present learning difficulties related to the English Language. The report addresses aspects that underlie the work with activities that aim to improve the quality of the undergraduate course and the teacher training process: the interaction and learning space, the use of technological resources, and the approach and use of the target language linked to the development of the participants’ autonomy. This proposal is theoretically based on studies developed by Harmer (2007), Bygate (2001), Larsen-Freeman (2001), and others. Data obtained through monitoring, and dialogue with those involved during the meetings point to the importance of the pedagogical support that is provided through the mentoring project, taking into consideration the existence of gaps and weaknesses in learning, which become evident at the beginning of the educational process in Higher Education.